Heavy Metal Accumulation in Some Plants in the Yesilirmak River Near the Antimony Mining Area Tokat, Northern Turkey - Duran, Mustafa; Kara, Yesim; Kivanc Akyildiz, Gurcay; Ozdemir, Adile (Asian Journal of Chemistry, 2010)
The levels of Sb, Cd, Pb, Zn and Cu in Phalaris arundinacea, Junculus inflexus, Polygonum percicaria, Carex riparia and Spirogyra sp. in the Yesilirmak River near the antimony mining area from june 2004 to November 2004 were determined. Antimony, cadmium, lead, zinc and copper uptake are not efficient for these 5 species when the availability of the elements in the water or sedimet are low or intermediate. The present results suggest that Phalaris arundinacea, Junculus inflexus, Polygonum percicaria, Carex riparia and Spirogyra sp. can not use as a bioindicator for Sb, Pb, Cd, Cu and Zn accumulation. These 5 heavy metals level remained below at which toxic effect would be likely to occur in potential concern about macroinvertebrate and fish.